2019
DOI: 10.1098/rsos.181278
|View full text |Cite
|
Sign up to set email alerts
|

Anodic behaviour of Cu, Zr and Cu–Zr alloy in molten LiCl–KCl eutectic

Abstract: The anodic dissolution behaviours of Cu, Zr and Cu–Zr alloy were analysed in LiCl–KCl at 500°C by anode polarization curve and potentiostatic polarization curve. The results show that the initial and fast-dissolving potentials of Cu are −0.50 and −0.29 V, and Zr are −1.0 and −0.88 V, respectively. But, in the Cu–Zr alloy, the initial and fast-dissolving potentials of Cu are −0.52 and −0.41 V, and Zr are −0.96 and −0.92 V, respectively. The potentials satisfy the selection dissolution principle that Zr in the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 17 publications
(26 reference statements)
0
11
0
Order By: Relevance
“…One promising methodology for recycling spent fuel Zralloy cladding is an electrometallurgical process that uses molten LiCl-KCl salt as a medium. [7][8][9][10][11][12][13][14][15][16][17][18][19] For such a process, the direct anodic dissolution of Zr-alloy cladding is the most straightforward strategy for administering Zr reactants into molten LiCl-KCl salts. 8,16 Since Zr-alloy cladding is generally composed of 97% or more of Zr; 8 it is essential to rigorously understand the anodic dissolution behavior of Zr in molten LiCl-KCl salt.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One promising methodology for recycling spent fuel Zralloy cladding is an electrometallurgical process that uses molten LiCl-KCl salt as a medium. [7][8][9][10][11][12][13][14][15][16][17][18][19] For such a process, the direct anodic dissolution of Zr-alloy cladding is the most straightforward strategy for administering Zr reactants into molten LiCl-KCl salts. 8,16 Since Zr-alloy cladding is generally composed of 97% or more of Zr; 8 it is essential to rigorously understand the anodic dissolution behavior of Zr in molten LiCl-KCl salt.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, our group 24 reported that the dissolution of Zr is accelerated rapidly at a more positive potential than the passivation potential proposed in previous publications. Cai et al 12 argued that the rapid increase in the dissolution current might be related to the transpassivation of Zr.…”
Section: Introductionmentioning
confidence: 99%
“…Even after most of the U was dissolved, the noble metals still remained in the anodic residue while Zr metal remained in the anode. Cai et al 15 explored Zr, Cu and Cu‐Zr alloy dissolution at anode in LiCl‐KCl melts, and the dissolution behavior, mechanism and kinetic data were investigated. Their results indicated that Zr was dissolved firstly in Cu‐Zr alloy to form Zr 4+ , while Cu was left in the alloy and not oxidized.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, due to its economic and environmental value, it is highly necessary to recycle zirconium present in residual and waste materials. 4 Among the methods available for recycling, much attention has been paid to electrochemical renement of zirconium in molten salts. Commonly, the electrorening of Zr occurs in alkali chloride, uoride, or chloride-uoride mixed fused melts.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, due to its economic and environmental value, it is highly necessary to recycle zirconium present in residual and waste materials. 4 …”
Section: Introductionmentioning
confidence: 99%